2020
DOI: 10.46586/tches.v2020.i4.416-442
|View full text |Cite
|
Sign up to set email alerts
|

Unrolled Cryptography on Silicon

Abstract: Cryptographic primitives with low-latency performance have gained momentum lately due to an increased demand for real-time applications. Block ciphers such as PRINCE enable data encryption (resp. decryption) within a single clock cycle at a moderately high operating frequency when implemented in a fully-unrolled fashion. Unsurprisingly, many typical environments for unrolled ciphers require protection against physical adversaries as well. Yet, recent works suggest that most common SCA countermeasures are hard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It remained uncertain, however, whether the small data-dependent differences in the leakage currents could be captured in sufficiently high quality to perform such attacks in real world experiments. Hence, several practical evaluations has been conducted on the subject [10][11][12][13][14][15][16][17]. It was not only confirmed that those attacks are indeed feasible, but also that this source of information leakage can become the most informative side channel in certain scenarios.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…It remained uncertain, however, whether the small data-dependent differences in the leakage currents could be captured in sufficiently high quality to perform such attacks in real world experiments. Hence, several practical evaluations has been conducted on the subject [10][11][12][13][14][15][16][17]. It was not only confirmed that those attacks are indeed feasible, but also that this source of information leakage can become the most informative side channel in certain scenarios.…”
Section: Introductionmentioning
confidence: 88%
“…In detail, it was shown that the effectiveness of static power attacks can be increased exponentially by manipulating the operating conditions of devices [14,16]. Previous works also demonstrated that common side-channel countermeasures against dynamic leakage behavior are less effective against its static counterpart [8,10,12,16,17]. For instance, due to a possibility to limit the noise in static power measurements, adversaries can exploit higher-order leakages of masked implementations with a lower data complexity [11,12,16].…”
Section: Introductionmentioning
confidence: 99%